An Observational Study of the Impact of a Computerized Physician Order Entry System on the Rate of Medication Errors in an Orthopaedic Surgery Unit. - Fabien Hernandez; Elyes Majoul; Carlota Montes-Palacios; Marie Antignac; Bertrand Cherrier; Levon Doursounian; Jean-Marc Feron; Cyrille Robert; Gilles Hejblum; Christine Fernandez; Patrick Hindlet (PLoS ONE, 2015)
To assess the impact of the implementation of a Computerized Physician Order Entry (CPOE) associated with a pharmaceutical checking of medication orders on medication errors in the 3 stages of drug management (i.e. prescription, dispensing and administration) in an orthopaedic surgery unit.A before-after observational study was conducted in the 66-bed orthopaedic surgery unit of a teaching hospital (700 beds) in Paris France. Direct disguised observation was used to detect errors in prescription, dispensing and administration of drugs, before and after the introduction of computerized prescriptions. Compliance between dispensing and administration on the one hand and the medical prescription on the other hand was studied. The frequencies and types of errors in prescribing, dispensing and administration were investigated.During the pre and post-CPOE period (two days for each period) 111 and 86 patients were observed, respectively, with corresponding 1,593 and 1,388 prescribed drugs. The use of electronic prescribing led to a significant 92% decrease in prescribing errors (479/1593 prescribed drugs (30.1%) vs 33/1388 (2.4%), p < 0.0001) and to a 17.5% significant decrease in administration errors (209/1222 opportunities (17.1%) vs 200/1413 (14.2%), p < 0.05). No significant difference was found in regards to dispensing errors (430/1219 opportunities (35.3%) vs 449/1407 (31.9%), p = 0.07).The use of CPOE and a pharmacist checking medication orders in an orthopaedic surgery unit reduced the incidence of medication errors in the prescribing and administration stages. The study results suggest that CPOE is a convenient system for improving the quality and safety of drug management.